Establishing the Legal Basis for Crypto Asset Confiscation: A Critical Study on the Challenges of Cybercrime Law Enforcement in Indonesia - Muhamad Rizqi Yudha Pratama; Chairul Muriman; Surya Nita (Transpublika Publisher, 2025)
Cryptocurrency offers high potential profits but also poses significant challenges for law enforcement, especially in the context of cybercrime. Cybercrime encompasses various illegal activities conducted through computer networks and the internet, such as online fraud, data theft, and money laundering. The purpose of this research is to analyze the current legal provisions in Indonesia governing the seizure of cryptocurrency in cybercrime cases and to examine legal solutions that can be implemented to address the regulatory gaps related to the seizure of cryptocurrency in cybercrime cases in Indonesia. This research employs a qualitative research method, using law enforcement theory as the analytical framework. The results indicate that the seizure of cryptocurrency in cybercrime cases in Indonesia is still relatively new and faces various challenges, including regulatory ambiguity and a lack of understanding among law enforcement regarding blockchain technology. Although cryptocurrencies are recognized as tradable digital commodities, existing legal provisions, such as those in the Indonesian Criminal Procedure Code (KUHAP) and the Attorney General's Regulation No. 7 of 2023, remain limited and require coordination with the Commodity Futures Trading Supervisory Agency (Bappebti) and physical traders. The absence of specific regulations regarding the procedure for seizing cryptocurrency calls for a comprehensive legal approach, including the formulation of clear regulations, strengthening the existing legal framework, and enhancing law enforcement capacity. With these measures, it is hoped that law enforcement against cybercrime can be conducted more effectively, providing legal certainty and protecting the public from the risks of cybercrime.